National Collegiate Athletic Association
Homepage of the National Collegiate Athletic Association (NCAA) of the USA. The National Collegiate Athletic Association is the organization through which the nation's colleges and universities speak and act on athletics matters at the national level. It is a voluntary association of more than 1,200 institutions, conferences, organizations and individuals devoted to the sound administration of intercollegiate athletics.